An Animal Trial on the Optimal Time and Intensity of Exercise after Stroke. Issue 8 (August 2020) - Zhang, Liying; Yang, Xiaofeng; Yin, Mingyu; Yang, Huaichun; Li, Lili; Parashos, Alexandra; Alawieh, Ali; Feng, Wuwei; Zheng, Haiqing; Hu, Xiquan
ABSTRACT: Introduction: Although exercise is a safe, cost-effective, and therapeutic poststroke therapy, the proper time window and dosage of exercise are still unknown. We aim to determine the optimal combination of time window and intensity of exercise by assessing infarct volume, neurological recovery, and underlying mechanisms in middle cerebral artery occlusion rats. Methods: The study contains two parts: the time-window and the dosage experiments. The time-window experiment assessed the effects of moderate-intensity exercise that was initiated at 24, 48, 72, 96 h and the control. In the dosage experiment, moderate and another two intensity exercise groups (low, high) were assessed. Forced wheel running was the exercise technique used. Infarct volume and neurological function (modified neurological severity scores [mNSS]) were measured. Inflammatory cytokines, cell death, and proliferation were further detected in the ischemic penumbra. Results: The time window part revealed that neither infarct volume nor mNSS was reduced in the exercise group initiated at 24 h. The other three groups with exercise initiated after 24 h had reduced infarct volume and reduced mNSS but those outcomes do not differ from each other. In the dosage part, the low- and moderate-intensity groups with exercise initiated at 48 h were both better than the high-intensity group in terms of infarct volume and mNSS at 14 d; however, there was no statistical difference between these low and moderate groups. Exercise initiated at 24 h or high-intensity promoted proinflammatory cytokines and cell death. Conclusions: Exercise at 24 h is harmful. Low- and moderate-intensity exercise initiated at 48 h poststroke appears to be the optimal combination for maximal functional recovery. Abstract : Supplemental digital content is available in the text.